Ablation of Refractory Ventricular Tachycardia Using Intramyocardial Needle Delivered Heated Saline-Enhanced Radiofrequency Energy: A First-in-Man Feasibility Trial. (1st July 2022) - Packer, Douglas L.; Wilber, David J.; Kapa, Suraj; Dyrda, Katia; Nault, Isabelle; Killu, Ammar M.; Kanagasundram, Arvindh; Richardson, Travis; Stevenson, William; Verma, Atul; Curley, Michael; ,
Abstract : Background: Ablation of ventricular tachycardia (VT) is limited by the inability to create penetrating lesions to reach intramyocardial origins. Intramural needle ablation using in-catheter, heated saline-enhanced radio frequency (SERF) energy uses convective heating to increase heat transfer and produce deeper, controllable lesions at intramural targets. This first-in-human trial was designed to evaluate the safety and efficacy of SERF needle ablation in patients with refractory VT. Methods: Thirty-two subjects from 6 centers underwent needle electrode ablation. Each had recurrent drug-refractory monomorphic VT after implantable cardioverter defibrillator implantation and prior standard ablation. During the SERF study procedure, one or more VTs were induced and mapped. The SERF needle catheter was used to create intramural lesions at targeted VT site(s). Acute procedural success was defined as noninducibility of the clinical VT after the procedure. Patients underwent follow-up at 30 days, and 3 and 6 months, with implantable cardioverter defibrillator interrogation at follow-up to determine VT recurrence. Results: These refractory VT patients (91% male, 66±10 years, ejection fraction 35±11%; 56% ischemic, and 44% nonischemic) had a median of 45 device therapies (shock/antitachycardia pacing) for VT in the 3 to 6 months pre-SERF ablation. The study catheter was used to deliver an average of 10±5 lesions per case, with an average of 430±295 seconds of radiofrequency time, 122±65 minute of catheter use time, and a procedural duration of 4.3±1.3 hours. Acute procedural success was 97% for eliminating the clinical VT. At average follow-up of 5 months (n=32), device therapies were reduced by 89%. Complications included 2 periprocedural deaths: an embolic mesenteric infarct and cardiogenic shock, 2 mild strokes, and a pericardial effusion treated with pericardiocentesis (n=1). Conclusions: Intramural heated saline needle ablation showed complete acute and satisfactory mid-term control of difficult VTs failing 1 to 5 prior ablations and drug therapy. Further study is warranted to define safety and longer-term efficacy. Registration: URL: https://www.clinicaltrials.gov ; Unique Identifier: NCT03628534 and NCT02994446.